1999
DOI: 10.1149/1.1391188
|View full text |Cite
|
Sign up to set email alerts
|

Formation of High Aspect Ratio Macropore Array on p-Type Silicon

Abstract: The fabrication of high aspect ratio macropore arrays on p-type silicon under optimum anodization conditions is demonstrated. The depth of the macropore can reach 400 µm with an aspect ratio of 100. The thickness of the pore wall is 1-2 µm. Presence of cationic surfactant in the electrolyte protects the pore walls and promotes the growth of the unidirectional macropores. The shape of preetched pits is critical for the formation of high aspect ratio macropores on p-type silicon. A self-supported silicon membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 3 publications
2
33
0
Order By: Relevance
“…Macropores were observed from 0.5 to 2 mA/cm 2 with etching time of 320 min; however, it was not possible to get deep and straight macropores unlike the known cases using surfactant or tenside added electrolyte [14]. The nanopores start to grow at 3 mA/cm 2 and their percentage of surface coverage increases up to 15 mA/cm 2 .…”
Section: Resultsmentioning
confidence: 94%
“…Macropores were observed from 0.5 to 2 mA/cm 2 with etching time of 320 min; however, it was not possible to get deep and straight macropores unlike the known cases using surfactant or tenside added electrolyte [14]. The nanopores start to grow at 3 mA/cm 2 and their percentage of surface coverage increases up to 15 mA/cm 2 .…”
Section: Resultsmentioning
confidence: 94%
“…So, pore is difficult to form using this type of dopant [40]. In contrast, the n-type silicon is efficient in collecting minority charge carriers with the help of illumination.…”
Section: New Research On Silicon -Structure Properties Technologymentioning
confidence: 99%
“…This is because of the disability of p-type substrate to control the charge carrier collection at the pore tips for anisotropic dissolution of silicon. So, ion can hardly attack the silicon during the pore formation [40]. Besides that, n-type silicon substrate is more efficient to collect the charge carrier with the assistance of photoluminescence to promote columnar pore structure due to the depletion of holes during pore passivity against dissolution [41].…”
Section: Figures 25-27mentioning
confidence: 99%
See 1 more Smart Citation
“…Easy to make; arrays of high aspect ratio can be obtained (Lehmann and Rönnebeck 1999;Chao et al 2000;Chazalviel et al 2002;Urata et al 2012) p-Si (org) Large macropore observed; decisive parameters are electrolyte resistivity, oxidizing power, and "passivation power" (Ponomarev and Lévy-Clément 2000;Christophersen et al 2001;Lust and Lévy-Clément 2002) n + -Si (aqu + oxidant) Small diameter (60-100 nm), highaspect-ratio macropores (Christophersen et al 2000c;Ge et al 2010) …”
Section: Macropore Formation Modelsmentioning
confidence: 99%